Results of transgastric drainage of fluid collections and postnecrotic pancreas cysts in patients with acute pancreatitis - V. G. Lubyansky; V. V. Nasonov (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. The issues of treating patients with acute fluid collections and postnecrotic cysts are still relevant at the present time. Optimization of the tactics of treatment of patients at the early stages of the formation of postnecrotic cysts makes it possible to reduce the percentage of complications.The OBJECTIVE was to develop diagnostic criteria for the formation of a cyst capsule at the early stages of acute pancreatitis, to determine the optimal timing and options for transgastric drainage of cysts.METHODS AND MATERIALS. The results of treatment of 62 patients were analyzed. All patients underwent computed tomography with bolus contrast and endoscopic ultrasonography. There were 2 groups of patients who underwent surgical treatment in the early and late periods. The results of endoscopic transgastric drainage of postnecrotic pancreatic cysts were analyzed.RESULTS. Based on the analysis of the results of treatment of patients with postnecrotic pancreatic cysts and acute peripancreatic fluid collections, the data of multispiral computed tomography and endoscopic ultrasonography at the stages of cyst formation, options and optimal timing of endoscopic transgastric drainage were determined. Causes of complications accompanying this method were identified and analyzed. The technique of transgastric drainage has been improved, methods for the prevention of complications have been proposed.CONCLUSION. The obtained results make it possible to recommend diagnostic criteria and a treatment algorithm for use in clinical practice.